Optimal handlebar position for track cyclists - Underwood, L.; Jermy, M. (Sports Engineering, 2013)
Wind tunnel tests were carried out on seven male and seven female track cyclists and the drag measured for their current favoured racing position and for different handlebar height and separation combinations deviating from their current favoured position. The handlebars were raised or lowered using spacers on the stem, and the elbow pads were placed wider apart or closer together using the adjustment slots on the pads. The degree to which adjustments were made was dependent on the equipment used, as not all handlebars had the same amount of adjustment. The drag area was calculated from the measured drag force and the results for drag area plotted for each athlete in each position to identify the optimal handlebar position for each athlete. The results showed that the handlebar height had a greater influence on the drag area compared to handlebar separation, but that there was a high degree of variability between athletes as to the optimal handlebar position.